2003
DOI: 10.1002/j.0022-0337.2003.67.3.tb03631.x
|View full text |Cite
|
Sign up to set email alerts
|

Views of Practicing Dentists Regarding a Mandatory Fifth Year of Training

Abstract: As part of a U.S. Health Resources and Services Administration-funded evaluation of the impact of federal funding on postgraduate general dentistry programs, a random sample of 6,725 dentists graduating in 1989, 1993, and 1997 were surveyed regarding practice patterns, advanced training, populations served, services provided, and their position on a mandatory fifth year of training. Responses (1,965) showed 48 percent supporting a mandatory year and 52 percent not supportive. Open-ended comments were provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In particular, many have noted that given the advances in science and technology, the nation's changing demographics, and the rising challenges in caring for vulnerable and underserved populations, the 4‐year undergraduate education is inadequate to fully prepare students not only with sufficient knowledge, but with the skills to integrate this knowledge into practice . Edelstein cites multiple researchers stating that “Evidence suggests that graduates’ perceptions of competency to treat vulnerable people including people with intellectual disabilities, very young children, disabled adults, elders, and frail elders ‐ relates directly to their lack of dental school experiences with these groups.…”
Section: Special Care Dentistry Is a Distinct Area Of General Dentistrymentioning
confidence: 99%
“…In particular, many have noted that given the advances in science and technology, the nation's changing demographics, and the rising challenges in caring for vulnerable and underserved populations, the 4‐year undergraduate education is inadequate to fully prepare students not only with sufficient knowledge, but with the skills to integrate this knowledge into practice . Edelstein cites multiple researchers stating that “Evidence suggests that graduates’ perceptions of competency to treat vulnerable people including people with intellectual disabilities, very young children, disabled adults, elders, and frail elders ‐ relates directly to their lack of dental school experiences with these groups.…”
Section: Special Care Dentistry Is a Distinct Area Of General Dentistrymentioning
confidence: 99%
“…A survey of 2,018 practicing dentists, published in 2003, found a roughly even split between supporters and non‐supporters of PGY‐1: 48% supported a mandatory year of training, and 52% were opposed 3 . Respondents who had completed an AEGD, GPR, or specialty program were more likely than other respondents to be supporters of PGY‐1, as were those holding positions in a community clinic, nursing home, or hospital clinic.…”
Section: Viewpoint 1: Pgy‐1 Provides Benefits That Support Making It mentioning
confidence: 99%
“…Garrison's study reported in 1991 that GPR‐trained practitioners tended to perform more oral surgery, periodontal surgery, complex endodontic procedures, and detailed patient work‐ups than their non‐GPR trained counterparts, while also needing to consult with specialists less frequently 5 . PGY‐1 programs that are hospital‐based also give residents more exposure and experience working with medically complex patients, while expanding residents’ clinical skill sets, knowledge base, and management skills related to emergency care for medically compromised and other patients 3 . In addition, PGY‐1 training makes it possible to tailor experiences based on the individual student's interests and practice goals.…”
Section: Viewpoint 1: Pgy‐1 Provides Benefits That Support Making It mentioning
confidence: 99%
See 2 more Smart Citations